1996
DOI: 10.1200/jco.1996.14.4.1306
|View full text |Cite
|
Sign up to set email alerts
|

Autologous peripheral-blood progenitor-cell support following high-dosechemotherapy or chemoradiotherapy in patients with high-risk multiple myeloma.

Abstract: High-dose chemotherapy or chemoradiotherapy followed by autologous PBPC support in MM is feasible and efficient. Further studies are needed to confirm these encouraging, although preliminary, results and to compare this technique with other therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
20
2
Order By: Relevance
“…Evaluating all MM stages (I to III) aged < 66 years (Table 5), the 4-year survival is 46% in our series and 40% (32-63%) in five Attal et al (1996);Marit et al (1996). bPresent series; Attal et al (1996).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Evaluating all MM stages (I to III) aged < 66 years (Table 5), the 4-year survival is 46% in our series and 40% (32-63%) in five Attal et al (1996);Marit et al (1996). bPresent series; Attal et al (1996).…”
Section: Discussionmentioning
confidence: 77%
“…The tables are compiled using median and 4-year survival, as the commonest data can be found in most BMT series (Fermand et al, 1993;Jagannath et al, 1993;Bjorkstrand et al, 1994;Cunningham et al, 1994;Harosseau et al, 1995;Attal et al, 1996;Bensiger et al, 1996;Marit et al, 1996;Vesole et al, 1996) and are useful for comparison with our series (Table 3). Additionally, for literature series, data on 4-year survival given by the authors (as a % of single series) have also been cumulated by calculating the actual percentage of patients of all series surviving 4 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 All the patients had aggressive MM defined as: (1) stage II or III MM at diagnosis according to the Durie-Salmon staging; 14 (2) plasmocytoma or stage I MM with no response to treatment or relapse after a previous response to treatment; and (3) plasma cell leukemia. The patients were eligible for HDCYC if they had aggressive MM, no history of cyclophosphamide-induced cystitis, plasma creatinine levels of less than 150 mol/l and normal hepatic and cardiac function.…”
Section: Patientsmentioning
confidence: 99%
“…1 Patients with high-risk multiple myeloma (MM) seem to benefit particularly from this type of treatment. [2][3][4][5] Moreover, in patients under the age of 65 with aggressive MM, the results of a recent randomized trial of the Intergroupe Francais du Myelome have shown the superiority of autologous transplantation over conventional treatment. 6 During the past few years, peripheral blood progenitor cells (PBPC) have progressively replaced bone marrow (BM) cells as the source of stem cells to rescue hematopoiesis after myeloablative treatment.…”
Section: Introductionmentioning
confidence: 99%